On the Nature of Isomeric Nonfluorescent Chlorophyll Catabolites in Leaves and Fruit – A Study with a Ubiquitous Phylloleucobilin and its Main Isomerization Product. Issue 11 (14th November 2017) - Moser, Simone; Scherzer, Gerhard; Kräutler, Bernhard
Abstract : The typical main products of chlorophyll (Chl) breakdown in higher plants are non‐fluorescent, colorless phyllobilins, named phylloleucobilins. These long elusive Chl‐catabolites are linear tetrapyrroles, whose structure elucidation has required thorough spectroscopic analyses. Interestingly, in recent LC/MS studies of leaf extracts, isomeric forms of phylloleucobilins were detected. The existence of isomeric phyllobilins may suggest incomplete stereo‐selectivity of catabolic processes, or isomerization processes in plant cells or in the analytes. Here we report a study with the phylloleucobilin NCC‐1, a basic Chl‐catabolite in extracts of leaves and fruit. NCC‐1 and its main isomerization product in aqueous solution were identified as 8 2 ‐epimers. Formation of 8 2 ‐epi‐NCC‐1 from NCC‐1 implies an unstable enol(ate)‐intermediate, which reverts to NCC‐1 or converts to 8 2 ‐epi‐NCC‐1. Such reversible epimerization reactions are a non‐biological in vitro feature of typical phylloleucobilins, and probably also take place in vivo . Abstract :